Forage potential of some Centrosema species in the Llanos Orientales of Colombia - Grof, B (1986)
The yield attributes of 18 accessions of Centrosema, comprising the species, C. macrocarpum, C. brasilianum, Centrosema sp. nov. were compared in two experiments under a cutting regime. Small, grazed swards of various Centrosema spp. sown with Andropogon gayanus in mixture were also studied, with the objective of identifting grass–legume associations adapted 1 to acid–soil savanna conditions and grazing. Stoloniferous forms of Centrosema sp. nov. (unnamed species) yielded well under cutting and were also especially good in the grazed swards, outyielding the other three Centrosema species in the high stocking, rate treatment (3 animals ha-1). From these studies in the Llanos Orientales of Colombia, it is concluded that several species of Centrosema are adapted to this high rainfall savanna ecosystem and that the stoloniferous forms can withstand heavy grazing.